CEPHEID RADIAL VELOCITIES - Samus, N. N.; Rastorgouev, A. S. (Одеські астрономічні публікації, 2017)
Some results of the programme of the measurements of the Cepheid radial velocities by using a correlational spectrometer are presented. The spectral binarity of the classical Cepheids MW Cyg and VZ Cyg is discovered. The orbital elements of the Population II binary Cepheid TX Del and of the classical binary cepheid DL Cas in an open cluster are determined more precisely. Preliminary orbital elements of MW Cyg are determined. By using the Baade-Wesselink method, the preliminary values of the radii of TX Del and DL Cas are determined.